2018
DOI: 10.1002/jia2.25089
|View full text |Cite
|
Sign up to set email alerts
|

Where have all the children gone? High HIV prevalence in infants attending nutrition and inpatient entry points

Abstract: Expanding routine early infant diagnosis screening beyond the traditional PMTCT setting to nutrition and inpatient entry points will increase the identification of HIV-infected infants. Careful reflection for appropriate testing strategies, such as maternal re-testing to identify new HIV infections and HIV-exposed infants in need of follow-up testing and care, at immunization and outreach services should be considered given the expectedly low prevalence rates. These findings may help HIV care programmes signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…Other studies have shown that inpatient and nutrition services are where infected children are found [37]. Expanding routine early infant diagnosis screening beyond the traditional PMTCT setting to outpatient and inpatient entry points will increase the identification of HIV-infected infants.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that inpatient and nutrition services are where infected children are found [37]. Expanding routine early infant diagnosis screening beyond the traditional PMTCT setting to outpatient and inpatient entry points will increase the identification of HIV-infected infants.…”
Section: Discussionmentioning
confidence: 99%
“…Even when testing coverage is relatively high, our sensitivity analyses show that further improving knowledge of HIV status has a substantial impact on reducing undiagnosed prevalence. Additionally, results suggest that because pregnant/breastfeeding women who are not on ART are likely to not be engaged with HIV services, testing children for HIV outside of formal infant testing programmes is critical [ 41 , 42 , 43 ]. Programmes offering routine, provider‐initiated HIV testing in medical settings outside of traditional pathways, such as nutrition, immunization, inpatient and TB clinics, have been found effective in identifying undiagnosed CLWH [ 41 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, results suggest that because pregnant/breastfeeding women who are not on ART are likely to not be engaged with HIV services, testing children for HIV outside of formal infant testing programmes is critical [ 41 , 42 , 43 ]. Programmes offering routine, provider‐initiated HIV testing in medical settings outside of traditional pathways, such as nutrition, immunization, inpatient and TB clinics, have been found effective in identifying undiagnosed CLWH [ 41 , 43 , 44 ]. A recent study offering routine HIV testing for infants up to 24 months of age in Uganda found that nutrition clinics have the highest undiagnosed HIV prevalence (9.8%), followed by traditional infant testing (3.8%), inpatient (3.5%), outreach (1.7%) and immunization (0.8%) settings, highlighting that settings frequented by younger and/or sicker children will have higher undiagnosed prevalence than general population settings (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for a false-positive result is of increasing concern as prevalence or transmission rates decrease. 3,4 For example, in a setting with mother-to-child transmission rates of less than 5%, the positive predictive value of a highly sensitive nucleic acid-based technology decreased to nearly 70%. 5 Fortunately, newer assays currently in use in the field have higher specificities with less dramatic decreases in positive predictive values.…”
mentioning
confidence: 99%